Peningkatan Mutu Pendidikan melalui SDM dan Sarana Pendukung Sekolah - Nurkholis .; Rafeyfa Azkiya Zakauha; Putri Salwa Azizah (CV. ITTC INDONESIA, 2026)
Human resources (HR) and school supporting facilities are essential factors in improving the quality of education. This study aims to analyze the strategic role of human resources and school supporting facilities in enhancing educational quality at MI Darul Hikmah Full Day School, Cirebon City. The study employed a descriptive qualitative approach using SOT triangulation techniques, including interviews, observations, and documentation. Data were collected through questionnaires administered to the principal, teachers, and educational staff, and were analyzed descriptively. The findings indicate that teacher professionalism, effective school management, and adequate educational facilities and infrastructure contribute positively to improving educational quality. Therefore, optimizing human resources and school supporting facilities should be continuously pursued to achieve high-quality and sustainable education